Recommendations for Assessment and Management of Health-Related Quality of Life in Patients with Mucopolysaccharidoses in Latin America - Giugliani,Roberto (2019)
Abstract Mucopolysaccharidoses (MPS) constitute a heterogeneous group of rare genetic disorders caused by enzymatic deficiencies that lead to the accumulation of glycosaminoglycans (GAGs). Clinical observations suggest a health-related impairment in quality of life in patients with MPS. Professionals with extensive experience in the care of patients with inborn errors of metabolism, such as MPS, held a meeting in April 2017 to discuss and propose recommendations for the evaluation and management of quality of life in MPS patients in Latin America. In the light of this scenario, the present work summarizes the content of the discussions and presents the recommendations produced at the meeting. The panel had suggested the use of the following tools for the assessment of health-related quality of life (HRQoL): Children's Health Assessment Questionnaire (CHAQ) for children and patients unable to express their feelings, Health Assessments Questionnaire (HAQ) and EuroQol 5 Domains (EQ-5D) scales for adult patients. Based on the scores verified in these scales, the panel proposes interventions that aim reducing the impairment of the quality of life in patients with MPS disorders.